2003
DOI: 10.1038/sj.onc.1206794
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 70 binding inhibits the nuclear import of apoptosis-inducing factor

Abstract: Heat shock protein 70 (HSP70) can inhibit apoptosis by neutralizing and interacting with apoptosis-inducing factor (AIF), a mitochondrial flavoprotein that translocates upon apoptosis induction to the nucleus, via the cytosol. Here, we show that only members of the HSP70 family interact with AIF. Systematic deletion mapping revealed the existence of three distinct functional regions in the AIF protein: (1) a region between amino acids 150 and 228 that binds HSP70, (2) a domain between residues 367 and 459 that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
192
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(204 citation statements)
references
References 29 publications
8
192
1
3
Order By: Relevance
“…RAC3 is physically associated with AIF in a protein complex containing the Hsp90, the immunophilin (FKBP52) and the microtubule-associated motor protein dynein It has been previously reported that H 2 O 2 -induced cell death involves the release of AIF from mitochondria and its import to the nucleus (Susin et al, 1999;Arnoult et al, 2002) and that Hsp70 specifically interacts with AIF and antagonizes apoptosis (Ravagnan et al, 2001;Gurbuxani et al, 2003). In addition, it is well known that Hsp70 is usually associated with Hsp90, which is involved in the regulation of signaling protein function and trafficking together with immunophilins and the microtubule-associated motor protein dynein (Pratt and Toft, 2003;Galigniana et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…RAC3 is physically associated with AIF in a protein complex containing the Hsp90, the immunophilin (FKBP52) and the microtubule-associated motor protein dynein It has been previously reported that H 2 O 2 -induced cell death involves the release of AIF from mitochondria and its import to the nucleus (Susin et al, 1999;Arnoult et al, 2002) and that Hsp70 specifically interacts with AIF and antagonizes apoptosis (Ravagnan et al, 2001;Gurbuxani et al, 2003). In addition, it is well known that Hsp70 is usually associated with Hsp90, which is involved in the regulation of signaling protein function and trafficking together with immunophilins and the microtubule-associated motor protein dynein (Pratt and Toft, 2003;Galigniana et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Caspase-8 and -9 activation was demonstrated by the measurement of caspase enzymatic activity and pro-caspase cleavage, and the inhibition results obtained with caspase-8 (Z-IETD-FMK)-and caspase-9 (Z-LEHD-FMK)-specific peptide inhibitors, and with biological HSV2-R1, and hsp70 inhibitors. HSV2-R1 blocks the activation of caspase-8 by an unknown mechanism [24], whereas hsp70 blocks the caspase-9-associated apoptotic process by inhibiting the release of cytochrome c from mitochondria, or by a yetto-be-characterized mechanism that occurs downstream of caspase-9 activation [12,21,30]. The facts that both caspase-8 and -9 were activated upon NS3∆50 expression following AdV infection, and that the BVDV NS3∆50-induced apoptosis correlated with cytochrome c release, suggest that caspase-8 likely acts indirectly at the mitochondria level, resulting in the release of cytochrome c from the mitochondria, and downstream activation of caspase-9 and effector caspases, rather than directly activating caspase-3 [38].…”
Section: Discussionmentioning
confidence: 99%
“…Triton-soluble proteins contained in rat brain extracts or in nuclear HeLa extracts were retained on these columns, eluted on an NaCl gradient beyond 500 mM NaCl and concentrated by buffer exchange, as described in detail by Gurbuxani et al The proteins were denatured, reduced, alkylated, subjected to proteolysis with trypsin, and then identified by LC-MS/MS, as previously described (Gurbuxani et al, 2003).…”
Section: Yeast Chronological Agingmentioning
confidence: 99%
“…We found that AIF binds to heat shock protein 70 (HSP70) and that this interaction can prevent AIF from translocating to the nucleus (Gurbuxani et al, 2003), where it exerts its proapoptotic action. This neutralizing interaction has been confirmed in vivo (Matsumori et al, 2005).…”
Section: Introductionmentioning
confidence: 99%